Interstitial Laser Capsulotomy for Refractory Obsessive-Compulsive Disorder-Lesion Size and Energy Deposition Determine Outcome. (1st September 2019) - Warnke, Peter C; Mahavadi, Anil; Grant, Jon
Abstract: INTRODUCTION: Current neurosurgical treatment of refractory severe Obsessive Compulsive Disorder either using radiosurgery, deep brain stimulation or lately focused ultrasound results in moderate and/or delayed responses. We describe the first case series in the literature applying high energy interstitial laser ablation (LITT) to successfully treat refractory OCD with immediate and sustained response. METHODS: Four patients with OCD underwent bilateral LITT capsulotomy from 2015 to 2019. All patients were reviewed by the Psychiatric Neurosurgery Board of the institution Inclusion criteria were based upon Yale-Brown Obsessive Compulsive Scale (Y-BOCS) score above 30 and inability to function in daily life. Each patient's pre- and postoperative partial and full Y-BOCS scores were collected. The partial Y-BOCS score was assessed 24 h post surgery. Ablation parameters such as total energy delivered, average power, and ablation volume were collected. Extent of connectome disruptions were assessed with volumetric diffusion tensor MRI. RESULTS: All patients had YBOCS scores between 31 and 40. Immediate improvement on partial Y-BOCS was noted in all patients 24 h post surgery. (Mean reduction of 83.3 + 20.1%) YBOCS scores after 3 mo went from 35.6 + 3.8 to 17.6 + 4.7, a more than 50% reduction. Lesion volumes were large with an average of 3.13 + 1.1 cc on T2 MRI. Energy deposited ranged from 402.75 to 868.5 Watts (700 C) consistently higher on the right side to create symmetric lesions ( P  < .01) .Orbito-frontal thalamic connections were reduced by more than 85% on DTI 24 h post surgery and consistently 3 mo postop. CONCLUSION: LITT is capable of creating large targeted lesions with real time MR monitoring leading to unprecedented almost immediate and extensive improvement in refractory OCD. Larger lesions due to higher energy deposition resulting in maximum disruption of the hyperactive circuitry underlying OCD are possible with LITT. Also, symptom reduction is superior to alternative techniques.